Hasan Hanafi's Thoughts on the Authenticity of God's Revelation - Amrin, Amrin; Supriyanto, Supriyanto; Suciyani, Suciyani (JURNAL INDO-ISLAMIKA, 2022)
The authenticity of God’s revelation is important to study because it might raise doubts among Muslim scholars when it is used for interpretation. The purpose of this study is to examine the authenticity of the revelation using Hasan Hanafi's thoughts as an Islamic thinker who has serious attention to the topic. This study uses a qualitative method and employs literature study. The approach is dialectic and historical. The results of the study show that Hasan Hanafi, in determining the authenticity of the revelation, carried out historical criticism that is free from theological, philosophical, mystical, and spiritual aspects. Hasan Hanafi put forward four instruments to authenticate. First, the text must be in verbatim. Second, the words of the revelation received by the Messenger must be written down at the time of recitation. Third, the transfer is through writing. Fourth, the process of transfer from oral medium to the written one must follow the rigid rules of transfer. He confirms that Qur'an qualifies as an authentic holy book when it is authenticated with historical criticism.